2014
DOI: 10.1089/hum.2012.253
|View full text |Cite
|
Sign up to set email alerts
|

Partial Correction of the CNS Lysosomal Storage Defect in a Mouse Model of Juvenile Neuronal Ceroid Lipofuscinosis by Neonatal CNS Administration of an Adeno-Associated Virus Serotype rh.10 Vector Expressing the Human CLN3 Gene

Abstract: Juvenile neuronal ceroid lipofuscinosis ( JNCL or CLN3 disease) is an autosomal recessive lysosomal storage disease resulting from mutations in the CLN3 gene that encodes a lysosomal membrane protein. The disease primarily affects the brain with widespread intralysosomal accumulation of autofluorescent material and fibrillary gliosis, as well as the loss of specific neuronal populations. As an experimental treatment for the CNS manifestations of JNCL, we have developed a serotype rh.10 adeno-associated virus v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…In a disease with global pathology such as MPSIIIC where the enzyme is not secreted and thus cannot cross-correct other cells, maximum cell transduction is required. A similar AAV-based approach has been developed in the non-cross correctable neurological disease CLN3, resulting in some disease correction, although neonatal delivery of AAV is often much more effective than delivery to adult mice ( Sondhi et al , 2014 ). Notably an intravenous AAV9 approach in CLN3 was only partly effective, underlining the difficulty of treating non-cross correctable neurological diseases ( Bosch et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a disease with global pathology such as MPSIIIC where the enzyme is not secreted and thus cannot cross-correct other cells, maximum cell transduction is required. A similar AAV-based approach has been developed in the non-cross correctable neurological disease CLN3, resulting in some disease correction, although neonatal delivery of AAV is often much more effective than delivery to adult mice ( Sondhi et al , 2014 ). Notably an intravenous AAV9 approach in CLN3 was only partly effective, underlining the difficulty of treating non-cross correctable neurological diseases ( Bosch et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Disease-relevant animal models are invaluable for the development and validation of therapies. However, encouraging preliminary data from gene therapy studies in murine forms 2,3,7,8 need careful consideration before proceeding to translation in human medicine because there are serious caveats with studies in mice. The lissencephalic mouse brain lacks major neuroanatomical structures prominent in the human brain and is very much smaller, 0.4 g versus 1.4 kg, and the neuropathology in many NCL mouse models varies from that seen in the analogous human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, AAV-mediated gene therapies have been reported to partially correct features of the disease phenotype in a model of CLN3 disease, which similar to CLN6 disease is caused by a defective transmembrane protein. Sondhi and colleagues showed a partial restoration of the neuropathological phenotype following multiple intracranial injections of AAVrh.10.CAG.hCLN3 in neonatal Cln3 ex7-8 mice (26). Bosch et al demonstrated that in young adult Cln3 ex7-8 mice intravenous administration of scAAV9 carrying CLN3 under the control of a weak neuronal promoter corrected the neuropathology up to 5 months post vector administration (27).…”
Section: Discussionmentioning
confidence: 99%